Memperkuat Daya Saing Bank Syariah Dengan Meningkatkan Kemampuan Teknologi Informasi - Amrizal Amrizal (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
Banking industry is very tight competition in all aspects. Results review from some literatures: journals and empirical data indicates that the banking industry has been applied information technology in order to provide excellent service to customers in the form of electronic transactions such as ATM, sms banking, e-commerce and so forth. Based on Bank Indonesia reports, the type of electronic transaction has been growing very rapidly between the transaction and Bilyetgiro Elekteronik Checks, ATM, Credit Card, Account Card Based (ATM and Debit Cards), Electronic Money, Delivery Chanel and RTGS. Those above transactions are relating to the Technology Information System and Integrated System. Integrated system is the combination of Hardskill which focus on knowledge and more to the integrity softskill (shidiq, trustworthy, tablig, fathonah). Islamic banks are ready to face competition both nationally and internationally, primarily face competition from the aspect of Integrated Systems. Bank Syariah Mandiri (BSM) developed e-banking features on an ongoing basis, among others